2005
DOI: 10.1016/j.amjhyper.2005.05.028
|View full text |Cite
|
Sign up to set email alerts
|

High Pulse Pressure Associated With Cardiovascular Events in Patients With Type 2 Diabetes Undergoing Hemodialysis

Abstract: Our results suggest that the strongest association of PP with CV morbidities should be considered in therapeutic strategies. These results show the necessity of targeting antihypertensive treatment to patients' predialysis blood pressure values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
9
1
Order By: Relevance
“…The optimal cutoff for PP was 60 mm Hg, which is consistent with the cutoff suggested in previous studies. 7,8,17,18 The VAT-free survival curve according to PP is illustrated in Figure 2. Patients with a PP460 mm Hg were more at risk for VAT than were patients with a PPo60 mm Hg (Po0.001, log-rank test).…”
Section: Resultsmentioning
confidence: 99%
“…The optimal cutoff for PP was 60 mm Hg, which is consistent with the cutoff suggested in previous studies. 7,8,17,18 The VAT-free survival curve according to PP is illustrated in Figure 2. Patients with a PP460 mm Hg were more at risk for VAT than were patients with a PPo60 mm Hg (Po0.001, log-rank test).…”
Section: Resultsmentioning
confidence: 99%
“…Tozawa et al (14) pointed out that the power of pulse pressure to predict total mortality was more accurate than that of SBP or DBP alone. London et al (12) described the importance of pulse pressure in considering BP control, and several studies reported that pulse pressure was an independent risk factor for CVE in the general population (25)(26)(27)(28)(29) and an independent predictor of risk for mortality or CVE in longterm HD patients (13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have reported the relationship between pulse pressure and mortality or cardiovascular events in HD patients (13)(14)(15)(16)(17). In this study, we studied in a prospective cohort whether WAB was a more useful prognostic marker in HD patients than one-point BP measurement and investigated which components of WAB were the most potent marker in evaluating the effect of hypertension on cardiovascular events (CVE) or all-cause mortality in HD patients.…”
mentioning
confidence: 99%
“…PP is influenced by the compliance of the aorta as well as stroke volume. High PP increases risk of cardiovascular events in an older population (Blacher et al, 2000;Fernández-Escribano Hernández et al, 2007;Foucan et al, 2005).…”
Section: Methodsmentioning
confidence: 99%